Examining the Impact of the Obama and Trump Candidacies on Right-Wing Domestic Terrorism in the United States: A Time-Series Analysis - Fortunato, Olivia (Journal of interpersonal violence, 2022)
Recent literature has described a rise in the activity of right-wing extremists in the United States. Several studies have examined this phenomenon in relation to the actions of President Trump. Comparatively, little research has examined the impact of the Obama presidency on right-wing extremism despite a peak in the number of right-wing extremist groups during his second term. Using a power-threat framework, this study examines the unique effects of the presidential candidacies and elections of Obama and Trump on the frequency of attacks committed by right-wing extremists in the U.S. as documented in the Global Terrorism Database (GTD). Autoregressive Integrated Moving Average (ARIMA) modeling is applied to monthly counts (n = 151) of 141 domestic terrorist attacks committed by right-wing extremists that occurred in the U.S. between June 3, 2006, and December 31, 2018. Consistent with the political threat hypothesis, our findings indicate that the re-election of President Obama was associated with a gradual, permanent increase in the frequency of attacks by right-wing extremists. Yet, none of the intervention components associated with his first candidacy or election were associated with statistically significant changes in right-wing terrorist attacks. In contrast, and in accordance with the emboldenment hypothesis, all intervention components associated with the candidacy and election of Donald Trump predicted permanent increases in the frequency of attacks?and most were abrupt in nature. In view of these findings, political leaders on the left and right must anticipate the ability of their rhetoric and behavior to both alienate and embolden extremist groups and individuals, particularly within the far-right. As our findings demonstrate, failure to do so risks contributing to increased activity among far-right extremists as a product of either political threat or emboldenment.